1997
DOI: 10.1111/j.1399-3054.1997.tb03468.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the alternative oxidase in limiting superoxide production by plant mitochondria

Abstract: Mitochondria isolated from the pericarp tissue of green bell pepper (Capsicum annuum L.) fruit and purified on a Percoll gradient produced superoxide in buffers aerated with oxygen. ADP and uncouplers of the electron transport chain reduced superoxide production. Disulfiram, an inhibitor of the alternative oxidase, enhanced superoxide production. Inhibitors of complex III had little effect on superoxide production by mitochondria which were insensitive to cyanide. Less superoxide was produced when dithiothreit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(73 citation statements)
references
References 25 publications
8
64
1
Order By: Relevance
“…Based on the fact that the inhibition of PUMP activity by the addition of ATP and BSA increases mitochondrial H 2 O 2 generation, it has been suggested that PUMP activity decreases the production of mitochondrial reactive oxygen species [140]. A similar regulatory function has been postulated for the alternative oxidase [141,142] and for rat UCP2, which could decrease the formation of reactive oxygen species under stress conditions by preventing overreduction of the respiratory chain [143]. Finally, we can postulate that plant UCPs could maintain the energy balance of the cell via the downregulation of ATP production and elimination of energy excess.…”
Section: Review Articlementioning
confidence: 97%
“…Based on the fact that the inhibition of PUMP activity by the addition of ATP and BSA increases mitochondrial H 2 O 2 generation, it has been suggested that PUMP activity decreases the production of mitochondrial reactive oxygen species [140]. A similar regulatory function has been postulated for the alternative oxidase [141,142] and for rat UCP2, which could decrease the formation of reactive oxygen species under stress conditions by preventing overreduction of the respiratory chain [143]. Finally, we can postulate that plant UCPs could maintain the energy balance of the cell via the downregulation of ATP production and elimination of energy excess.…”
Section: Review Articlementioning
confidence: 97%
“…3,4 Though mitochondria are the major source of ROS production in mammalian cells, in green tissues its contribution for ROS is not effective. 5 The mitochondrial electron transport chain can produce ROS, which can transfer a single electron to oxygen and produce O 2 -. The mitochondrial alternative oxidase (AOX) catalyses the O 2 -dependent oxidation of ROS.…”
Section: Production Of Reactive Oxygen Intermediates In Plantsmentioning
confidence: 99%
“…One proposed function of the AP is to prevent the UQ pool from becoming overly reduced, which can result in production of active/reactive oxygen species (ROS; Boveris and Cadenas, 1982;Purvis, 1997;Møller, 2001). Transgenic tobacco plants over-expressing tobacco AOX show lower production of ROS in the mitochondria (Maxwell et al, 1999) and the tobacco Aox1 gene is induced by application of hydrogen peroxide (Maxwell et al, 2002).…”
Section: Introductionmentioning
confidence: 99%